Qualidade de vida em portadores de paralisia cerebral: associação com nível funcional e aspectos sócio-demográficos - Arthuso, Claudini Bastos [UNESP] (2014)
Cerebral Palsy (CP) is a major cause of chronic disability in childhood as having sequel motor disorders that are accompanied by disturbances of sensation, perception, cognition, communication and behavior, and secondarily by musculoskeletal disorders. This cross-sectional study aimed to evaluate the quality of life (QOL) of children with Cerebral Palsy (CP) and its relation to the functional level (Gross Motor Function Classification System GMFCS), sociodemographic characteristics and frequency physiotherapy beyond his years start. The sample consisted of 71 primary caregivers and 45 children. To assess quality of life instruments Child Health Questionnaire were used - Parent Form 50 (CHQ PF50) and Autoquestionaire Qualité de Vie Efant image (AUQEI) functional level, demographic data and related rehabilitation (frequency and age of onset in physiotherapy) were used in order to check how much they affect the quality of life of the individual with cerebral palsy. Children and primary caregivers were assessed at Rehabilitation Support Unit Hospital Estadual de Bauru (HEB). Descriptive analysis of demographic data such as age, education, household income and other was performed. For categorical variables we used the Tukey test when significance was found. The Pearson correlation was used to correlate demographic data with the scores obtained by assessing the quality of life. The mean age of children was 9.83 (SD 1.5) and the majority of children were male (54.9%). As a result the physical score was the most affected mainly the most severe form of PC when compared to other levels. From the point of view of the children there was no significant difference between the levels. Regarding physical therapy was observed that the higher the frequency in physiotherapy, better quality of life indices. Conclusion: in the present study it was concluded that the quality of life evaluated from the point of view ...